Educação matemática: propostas e desafios - Marcelo Carvalho Borba; Silvana C. Santos (EccoS – Revista Científica)
In this paper, we discuss some aspects of Mathematics education, seen as a realm of inquiry, and we show how this field has strong ties both with mathematics and with education, as well as other areas. We also aim to illustrate through an example related to research regarding mathematics distance education how Mathematics is transformed when different media become a part of the processes of knowledge production. Finally, it is presented some ideas about how research and reflections on their findings generate new research projects.